Formação docente e inclusão de alunos com transtorno do espectro autista em escolas estaduais de Ponta Grossa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Inclusive education is a crucial issue in the contemporary educational scenario. It seeks to ensure that all students, regardless of their differences and needs, have access to quality education. In Brazil, the right to equal education is guaranteed to all under the constitutional and legal provisions. However, the traditional teaching process often does not adequately meet the demands of the student body. Among these demands, the inclusion and education of children with Autism Spectrum Disorder (ASD) stands out. In this context, public educational policies are necessary, aiming at training teachers and promoting inclusive practices in schools. Considering that teachers play a fundamental role in implementing inclusive education in everyday school life, it is essential to analyze the continuing education of these professionals, considering their preparation to deal with students with ASD. Therefore, it is necessary to question whether the continuing education offered to them is sufficient for the exercise in the current inclusive context of basic education. Based on this issue, this study aimed to analyze the continuing education of teachers regarding the learning of students who are the target audience of special education from the perspective of inclusive education. Specifically, we sought to: a) provide data capable of identifying the main gaps in the initial and continuing education of teachers in relation to Inclusive Education for students with Autism Spectrum Disorder (ASD) in state schools in Ponta Grossa; b) analyze teachers' perceptions about their levels of preparation to work with students with ASD based on their practical experiences and training received; c) identify current public policies for continuing education of teachers for Inclusive Education, with an emphasis on ASD, in the state education system; d) propose recommendations for improving the initial and continuing education of teachers. To this end, a qualitative-quantitative research was carried out to understand the history of the concept of ASD and to validate the need to expand public policies for inclusion and promotion of equality. Furthermore, field research was used to collect data via questionnaires from elementary school teachers in ten state schools located in the city of Ponta Grossa, state of Paraná. The results were summarized in a multi-paper format, with the first article being a component of this dissertation on the evolution of the concept of autism spectrum disorder and the second article on the initial and continuing education of teachers in state schools in Ponta Grossa/PR. Regarding the first of these articles, the results indicated that the history of ASD portrays scientific and social progress for improving the quality of life of those diagnosed with ASD and those with whom they live. In another turn, the second stage of the study resulted in evidence that there is a considerable gap in teacher preparation, reflecting the need to update continuing education in special education and inclusive education. It was concluded, in the end, that the continuing education of basic education teachers is deficient and they do not feel capable, as a rule, of working with students with ASD, therefore, it is necessary to update initial training, still during graduation, and continued training, through public incentive policies.
Keywords: Formação docente; Inclusão; Transtorno do Espectro Autista; Educação especial; Educação inclusiva; Teacher training; Inclusion; Autism Spectrum Disorder; Special education; Inclusive education; CNPQ::CIENCIAS SOCIAIS APLICADAS